2000
DOI: 10.1046/j.1365-2249.2000.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased interferon-gamma (IFN-γ), IL-10 and decreased IL-4 mRNA expression in peripheral blood mononuclear cells (PBMC) from patients with systemic lupus erythematosus (SLE)

Abstract: SUMMARYCytokines are important regulators of lymphocyte function in SLE. However, the profile of Th1 and Th2 cytokines produced by circulating lymphocytes in human SLE has not been clearly elucidated. The aim of the present study was to characterize the gene expressions of the Th1-type cytokine IFN-g, and the Th2-type cytokines IL-10 and IL-4 in PBMC of 15 patients with SLE and 10 healthy individuals by a semiquantitative reverse transcriptase polymerase chain reaction (RT-PCR). Our results showed that express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 55 publications
9
102
3
Order By: Relevance
“…Increased IFN-␥ mRNA and decreased IL-4 gene expression are found in PBMCs taken from SLE patients (5). Th1 cytokines, including IFN-␥, are present in tissue of SLE patients with the most severe disease, with enhanced production of this cytokine by peripheral blood cells and in the kidneys of patients with severe lupus glomerulonephritis, compared with individuals with milder renal disease (6,7).…”
Section: Il-10 Regulates Murine Lupusmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased IFN-␥ mRNA and decreased IL-4 gene expression are found in PBMCs taken from SLE patients (5). Th1 cytokines, including IFN-␥, are present in tissue of SLE patients with the most severe disease, with enhanced production of this cytokine by peripheral blood cells and in the kidneys of patients with severe lupus glomerulonephritis, compared with individuals with milder renal disease (6,7).…”
Section: Il-10 Regulates Murine Lupusmentioning
confidence: 99%
“…This cytokine has been presumed to be an important modulator of disease activity in human SLE. Patients with lupus produce large amounts of , with enhanced gene expression in PBMCs (5), and its serum level correlates with disease activity (19 -21). While the precise role of IL-10 in the pathogenesis of lupus remains uncertain, studies have suggested that this cytokine is pathogenic both in humans and in mice with disease.…”
Section: Il-10 Regulates Murine Lupusmentioning
confidence: 99%
“…99 Among SLE patients, the numbers of IL-10-producing cells are increased in the peripheral blood, resulting in these patients having an abundance of pathogenic autoantibodies. [100][101][102] Moreover, lupus-prone mice that are administered recombinant IL-10 develop accelerated autoimmune disease. 103 For these reasons, IL-10 is a possible candidate gene in lupus susceptibility.…”
Section: Interleukin-10mentioning
confidence: 99%
“…This may, in turn, affect tolerance against self-antigens and lead to a dysfunction of the immune system. [3][4][5] Large numbers of B-1a cells were found in subjects with chronic periodontitis, Sjö gren's syndrome and rheumatoid arthritis. [6][7][8][9][10] Interleukin (IL)-10 is an important cytokine in the regulation of immune responses and was earlier considered to be mainly anti-inflammatory.…”
Section: Introductionmentioning
confidence: 99%